2011
DOI: 10.1007/s10157-011-0472-7
|View full text |Cite
|
Sign up to set email alerts
|

Nephrologist care for 12 months or more increases hemodialysis initiation with permanent vascular access

Abstract: Early referral was shown to be advantageous for increasing the likelihood of availability of a permanent VA, even after patients who had been followed up for less than 3 months by nephrologists were excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Numerous studies indicated the importance of early referral to a nephrologist. In particular, these studies reported an association between late referral for CKD care and adverse outcomes, such as choice of dialysis modality [ 4 , 5 ], inpatient start or emergent initiation of renal replacement therapy [ 4 , 6 ], use of a hemodialysis catheter [ 6 , 7 ], and mortality [ 6 , 8 , 9 ]. Other studies reported that the advantages of early referral are provision of appropriate therapy based on diagnosis, slowing or arresting the progression of CKD, prevention and management of comorbid conditions and CKD-specific complications, planning and preparation for maintenance dialysis, and psychosocial support[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicated the importance of early referral to a nephrologist. In particular, these studies reported an association between late referral for CKD care and adverse outcomes, such as choice of dialysis modality [ 4 , 5 ], inpatient start or emergent initiation of renal replacement therapy [ 4 , 6 ], use of a hemodialysis catheter [ 6 , 7 ], and mortality [ 6 , 8 , 9 ]. Other studies reported that the advantages of early referral are provision of appropriate therapy based on diagnosis, slowing or arresting the progression of CKD, prevention and management of comorbid conditions and CKD-specific complications, planning and preparation for maintenance dialysis, and psychosocial support[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, despite the enormous disparity in nephrologists per capita, rural patients are significantly more likely to have a functional AVF at first outpatient dialysis. This finding was seen despite the lack of significant differences in pre-ESRD nephrology care, which in other studies has been associated with increased placement of AVFs (15). Curiously, other factors associated with improved AVF placement were greater availability of nephrologists and surgeons for a given population (16), along with coordinated care (17), a factor not discernible from the database.…”
mentioning
confidence: 67%
“…The successful creation and use of an AVF requires a coordinated multidisciplinary team of nephrologists, nurses, surgeons, the patient, and the patient's family. Referral to a nephrologist close to the time of initiation of dialysis is a common reason for lower AVF use because it does not allow for sufficient time to complete the required planning and preparation . Although the incidence of CKD has increased gradually in China, there is low awareness and insufficient treatment due to medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…In China, AVFs are only used in approximately 20% of incident patients prior to hemodialysis, whereas approximately 80% of patients with chronic kidney disease (CKD) are initiated with a CVC . High rates of AVF use are possibly a result of early referrals to nephrologists . In addition, many patients do not receive follow up due to insufficient awareness of the disease and the high cost of doctor's visits.…”
mentioning
confidence: 99%